Relationship Between Method and Duration of Contraception Usage to Subjective Health Complaints - Nabella Kusuma (Universitas Airlangga, 2017)
Subjective health complaints is identified is symptoms and uncomfortable feeling felt by the respondents. Health Complaint is the most common cause of acceptor stops using contraception. The aim of this study was to exsamine between of subjective health complaints related by contraception method and duration of contraception usage. This study was observational analytic with cross sectional design. The sample of study were acceptor living at RW 6 Kalitengah Sidoarjo district and using simple random sampling technique to collect the data. Statistical test using chi square to determine the relationship between variables. The study showed that most of the respondents were aged > 35 years old (62,5%), educated as high as high school (59,7%), were housewife (70,8%). Statistic test using chi square showed that there was relationship between contraception method (p = 0.0098) and the duration of contraception usage (p = 0.012) with subjective health complaints. Hormonal contraceptive methods may increase the risk of 4,05 times to experience subjective health complaints compared with respondents who use non-hormonal contraception. Respondents with long ≤ 5 years of contraceptive use may increase the risk of 7,82 times to experience subjective health complaints compared with respondents who used the contraceptive for > 5 years. It is concluded that contraception method and the duration of contraception usage are related to subjective health complaints. It is recommended for the midwives to educate respondents who were using hormonal contraception to change into using non hormonal contraception when have complaint. Keywords: contraception method, usage duration, subjective health complaints